Energy deficiency promotes rhythmic foraging behavior by activating neurons in paraventricular hypothalamic nucleus - Wu, Shanshan; Wang, Jing; Xu, Yang; Zhang, Zicheng; Jin, Xinchen; Liang, Yixiao; Ge, Yueping; Zhan, Huidong; Peng, Li; Luo, Dandan; Li, Mengzhu; Bi, Wenkai; et al. (Frontiers in Nutrition, 2023)
Dysregulation of feeding behavior leads to a variety of pathological manifestations ranging from obesity to anorexia. The foraging behavior of animals affected by food deficiency is not fully understood. We describe here a unique mouse model of foraging behavior. Utilizing Home-Cage system to monitor mice behaviors in real-time, we unveiled that food deprivation significantly increases the general activities of mice with a daily rhythmic pattern, particularly foraging behavior. The increased foraging behavior is potentiated by food cues (mouthfeel, odor, size, and shape) and energy deficit, rather than macronutrient protein, carbohydrate, and fat. Notably, energy deficiency increases nocturnal neuronal activity in paraventricular hypothalamic nucleus (PVH), accompanying a similar change in rhythmic foraging behavior.Activating neuronal activity in PVH by chemogenetic approach enhances the amplitude of foraging behavior in mice. Conversely, inactivating neuronal activity in PVH by chemogenetic approach decreases the amplitude of foraging behavior and impairs the rhythm of foraging behavior. These results illustrate that energy status and food cues regulate the rhythmic foraging behavior via PVH neuronal activity. Understanding foraging behavior provides insights into the underlying mechanism of eating-related disorders.